Analysis of the immersion time of nettle fiber in NaOH and silane on the hardness and toughness of composite hybrid materials - Suarsana, K.; Suryawan, I.G.P.A.; Sunu, P.W.; Triadi, A.A.A. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2022)
The advantages of stinging nettle fiber (Urtica dioica L.) properties as a substitute for synthetic fibers for reinforcing composite materials are its strength and light weight compared to other natural fibers. This study aims to find the mechanical properties of hybrid composites reinforced with stinging nettle fiber based on immersion treatment of the fibers with chemical solutions. The mechanical properties studied include the hardness and toughness of the hybrid composite. This paper examines the effect of fiber immersion time in NaOH and Silane coupling agent solutions at concentrations of 3% and 9% which are used as reinforcement for hybrid epoxy resin composites. Variations of fiber immersion time in NaOH and Silane solutions: 30, 60, 90, and 120 minutes. Hybrid composite was produced by hand lay-up molding method. The results showed that the highest value of hardness was 88,254 VHN and toughness was 7,459 kJ/m2 at 9% immersion. NaOH solution can remove impurities and lignin in the fiber and Silane coupling agent can form strong bonds because it has a hydroxy group. Based on the results of the study, it can be concluded that the hardness and toughness of the hybrid composite reinforced by stinging nettle fiber has higher hardness and toughness at 9% NaOH and Silane treatment with immersion time of 120 minutes.